INTRODUKSI KONSTRUK GEN CSNITR1-L DENGAN PROMOTOR UBIQUITIN MELALUI AGROBACTERIUM TUMEFACIENS DAN DETEKSI MOLEKULERNYA PADA PADI KULTIVAR NIPPONBARE - Enngarini, Wening; Polosoro, Aqwin; Sustiprijatno, Sustiprijatno; Trijatmiko, Kurniawan Rudi (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTNitrogen based fertilizers such as urea and NPK are primary needs for rice farmers. To get significant improvement of crop yield, the more quantity of fertilizers are applied. It make negative impact for surrounding environment. Based on that, the efforts should be done to suppress the demand of fertilizers such as by developing Nitrogen Use Efficiency crops. CsNitr1-L is one of gene that related to Nitrogen Use Efficiency trait in plant. The objectives of this research are to develop the construction of CsNitr1-L gene candidate in pCAMBIA1300-Ubi1 promoter and to obtain the transformants of rice cultivar Nipponbare which contain the construction of CsNitr1-L gene candidate. The construction of pCAMBIA1300::Ubi1::CsNitr1-L has successfully assembled and was transformed to immature embryo of rice cultivar Nipponbare using Agrobacterium tumefaciens strain LBA4404. It was obtained 146 lines of T0 Nipponbare. PCR analysis of T0 Nipponbare lines showed that 66 of them was identified as positive T0 lines contained hptII and CsNitr1-L genes. Transformation efficiency obtained was 11,9%. The result of analysis copy number using Southern Hybridization in positive PCR of T0 lines randomly indicated that 4 lines have a single copy of transgene. Based on these results, it can be concluded that CsNitr1-L gene construct was successfully introduced into the genome of the rice plant cultivar Nipponbare and the positive PCR of T0 lines containing the gene of hptII and CsNitr1-L, also a single copy of the transgene was obtained.Keywords: Nitrogen use efficiency trait, gene construction, rice kultivar Nipponbare